An integrative approach to dementia care - Warren, Alison (Frontiers in Aging, 2023)
As the aging population continues to increase, Alzheimer’s disease and related dementias are becoming a global health crisis. The burdens experienced by the person living with dementia, their caregivers, healthcare, and society persist unabated. Persons with dementia represent an important population in need of a tenable care plan. Caregivers need the tools with which to properly care for these persons and to mitigate their own stress response. A viable healthcare model utilizing integrated approaches to care for persons with dementia is in overwhelming demand. While much research is focused on a cure, it is equally important to address the difficulties faced by those currently affected. One approach is to incorporate interventions to increase quality of life within the caregiver-patient dyad via a comprehensive integrative model. Improving daily life of the persons with dementia, along with their caregivers and loved ones may aid in attenuating the pervasive psychological and physical impacts of this disease. A focus on interventions that provide neural and physical stimulation may facilitate quality of life in this regard. The subjective experience of this disease is challenging to capture. The relationship between neurocognitive stimulation and quality of life is at least, in part, therefore speculative. This narrative review aims to explore the efficacy and evidence-base of an integrative approach to dementia care in facilitating optimal cognition and quality of life outcomes. These approaches will be reviewed alongside person-centered care that is fundamental to integrative medicine, including exercise; music; art and creativity; nutrition; psychosocial engagement; memory training; and acupuncture.